Blood pressure to height ratio for screening hypertension among Indonesian adolescents - Partini Pudjiastuti Trihono; Jeanne Laurensie Sihombing; Rismala Dewi (Indonesian Pediatric Society, 2023)
Background Pediatric hypertension is an emerging health issue due to its increasing prevalence. Age-, gender-, and height-specific blood pressure percentiles have been widely used as a primary tool for detection of hypertension in the pediatric population. However, this method is too complicated to be used in general pediatric practice. The blood pressure to height ratio has been proposed as a practical tool to detect hypertension in children. Objective To evaluate the accuracy of blood pressure to height ratio to be used as a tool for screening high blood pressure in Indonesian adolescents. Methods This diagnostic test study using data from the 2013 Indonesia Basic Health Research (Riset Kesehatan Dasar/RISKESDAS) report included 39,057 adolescents aged 15-18 years with complete data on age, gender, weight, height, and blood pressure. Blood pressure values were classified using the 2017 American Academy of Pediatrics (AAP) hypertension clinical guidelines. Blood pressure to height ratio was calculated as mmHg/cm body height. A receiver-operator characteristics (ROC) curve analysis was performed to assess the accuracy of systolic blood pressure to height ratio (SBPHR) and diastolic blood pressure to height ratio (DBPHR) for screening high blood pressure in adolescents. The optimal cut-off points, sensitivity, and specificity of SBPHR and DBPHR were calculated. Results The optimal cut-off points for defining elevated blood pressure in male adolescents aged 13-18 years were SBPHR 0.69 for male adolescents (sensitivity 96%, specificity 80%) and DBPHR 0.46 (sensitivity 97%, specificity 84%). In female adolescents, the optimal cut-offs were SBPHR 0.72 (sensitivity 97%, specificity 82%) and DBPHR 0.48 (sensitivity 98% and specificity 79%). Conclusion Blood pressure to height ratio is a practical method with high sensitivity and specificity for detecting elevated blood pressure in Indonesian adolescents aged 15 to 18 years.